A Rare Complication of Infraorbital Nerve Hyperesthesia in Surgically Repaired Orbital Fracture Patients. Issue 3 (May 2017) - Cho, Seong Eun; Shin, Ho Seong; Tak, Min Sung; Kang, Sang Gue; Lee, Yong Seok; Kim, Hyun Sung; Kim, Chul Han
Abstract : Abstract: Injury to the peripheral sensory branches of the trigeminal nerve can follow a wide variety of craniofacial injuries. Many patients with facial fractures complain about the symptom of numbness to the distribution of injured nerve, which is indicative of hypoesthesia. Hyperesthesia involving the infraorbital nerve is rare in comparison to hypoesthesia secondary to facial trauma. The authors report on 2 patients with infraorbital nerve hyperesthesia in surgically repaired orbital fracture patients. Surgical decompression of the infraorbital nerve led to rapid resolution of hyperesthesia. To the best of our knowledge, these were rare cases of patients who presented with persistent hyperesthesia. Clinician should perform early surgical decompression of the infraorbital nerve in patient with persistent hyperesthesia of the infraorbital nerve.